Data Privacy and Security in Health Informatics: Ethical and Legal Considerations - Mohammed Javeedullah (Information Technology and Science (ITScience), 2025)
Through its approach of digital health data management health informatics has brought extensive transformation to healthcare while delivering improvements to clinical procedures and treatment effectiveness and work processes. Health data management transformation creates substantial privacy and security problems with sensitive health information. This paper examines fundamental health data management problems by analyzing legal standards and security systems together with ethical concepts and innovative technology systems. Health data management practices need to follow ethical principles which include autonomy and beneficence and non-maleficence and justice and these practices must abide by legal frameworks which encompass HIPAA and GDPR. Health data protection requires three essential elements which involve encryption technology with access control systems and audit trail functionality. New privacy along with security challenges emerge from the implementation of block chain and AI and cloud computing technologies which bring opportunities to innovate. This text highlights the requirement for sensible approaches which aim to deliver safe application of technology alongside well-protected information and trusted patient relations and ethical healthcare delivery within advancing digital health settings.